A Educação escolar em Fordlândia-Pa e a influência da Companhia Ford Industrial do Brasil - 1931 a 1945 - KLUSKA, Caren Alessandra (Universidade Federal do Oeste do Pará, 2023)
This study deals with school education in Fordland - PA, in the context of the validity of the Ford Industrial Project of Brazil in the Amazon (CFIB), from 1931 to 1945. The CFIB was created in 1927, with the purpose of initiating The plantation of rubber trees in a native environment, in the State of Pará, aiming to supply the auto industry of Henry Ford in the United States. A city was set up in the middle of the forest and named Fordland, with houses, sawmill, power plant, water supply system, leisure areas and a school. The problem to be answered with this research refers to the educational and practical conceptions resulting from the Fordland School Group. The objective is to understand and record the relationships with the political and educational changes of the period, seeking to understand the school's particularities and its relations with the CFIB and the State Government of Pará. This is a qualitative research in the case study modality, Methodological procedures, the use of images and videos from the web, collection and analysis of primary documentary sources, and interviews with three former students of Fordlândia School Group. It has as main references the works of Amorim (1995), Costa (2012), Dean (1989), Grandin (2010), Jackson (2011), Lourenço (1999), Maia (2002) and Santos (1980) Of historical aspects related to Fordlandia, and in the historical educational field: Aranha (2006), Coelho (2008), Ribeiro (2010), Pereira (2016), Romanelli (2007) and Xavier (2004). After collecting, analyzing and triangulating the data, the Fordland School Group, although public, attended only to the children of CFIB workers and, even though it was within the Fordlandia concession, was not controlled by the company, responding administratively and Pedagogically to the government of the State of Pará. The company provided school uniforms and other materials when requested, if present in solemn sessions and paid the teachers of the Group, which were sent by the State Department of Education and Culture. The presence of this educational institution was used as marketing and advertising, a means of attracting workers to the rubber plantations. However, school dropout rates were high. The practices developed were based on the traditional teaching chain, with the frequent use of palmat and sabatina, according to the learning that the teachers had received in the normal schools where they had graduated. The records found in books on the issue of correspondence, visitor impressions, student promotion, solemn sessions held, and enrollment records in the Fordland School Group archives were fundamental for the understanding of its unique aspects and for the objectives proposed in the Achieved.